(3GdPNjQI aj aQhY GdMfajIs - (3HQgGf GdOjf YHO GdYRjR Hf YeQ GdHNGQjs; (3GdeQZjfGfj , eMehO Hf CMeO Hf YHO GdYRjR Hf YeQ Hf eGRg, HQgGf GdOjf,J (B616 (3g` s
(3ChdgG (B:s
(3cJGH GdUjO s
(3BNQgG (B:s
(3BNQ cJGH GdHjhY s
(3ef GdfSNI GdSGHbIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdMfajs